2007
DOI: 10.1111/j.1365-2567.2007.02619.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of lipopolysaccharide and Gram‐positive bacteria induced cytokine and chemokine production in macrophages by Gαi proteins

Abstract: Summary Heterotrimeric Gi proteins play a role in signalling activated by lipopolysaccharide (LPS), Staphylococcus aureus (SA) and group B streptococci (GBS), leading to production of inflammatory mediators. We hypothesized that genetic deletion of Gi proteins would alter cytokine and chemokine production induced by LPS, SA and GBS stimulation. LPS‐induced, heat‐killed SA‐induced and heat‐killed GBS‐induced cytokine and chemokine production in peritoneal macrophages from wild‐type (WT), Gαi2–/– or Gαi1/3–/– mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 41 publications
4
24
0
Order By: Relevance
“…3). The latter observation is in agreement with the findings of Fan et al (39), who suggested that Ga i2 and Ga i3 are both involved in LPSinduced cell activation. However, we also note that Ga i3 -deficient mice exhibit an increased accumulation of macrophages in lung tissue in response to LPS ( Fig.…”
Section: Discussionsupporting
confidence: 83%
“…3). The latter observation is in agreement with the findings of Fan et al (39), who suggested that Ga i2 and Ga i3 are both involved in LPSinduced cell activation. However, we also note that Ga i3 -deficient mice exhibit an increased accumulation of macrophages in lung tissue in response to LPS ( Fig.…”
Section: Discussionsupporting
confidence: 83%
“…Recently, whole S. suis type 2 was shown to induce CCL2 production by murine DCs (12) and CCL3 production by total mouse splenocytes (unpublished data). Similarly, studies have shown that whole GBS type III stimulates CCL2 and CCL3 secretion by murine macrophages and/or DCs (85,86). Our observations with purified CPSs allow a better interpretation of previous data showing different patterns of chemokine production obtained with total leukocytes, monocytes, and/or DCs cultured in the presence of whole S. suis type 2 or GBS types III and V and their respective nonencapsulated mutants.…”
Section: Figsupporting
confidence: 51%
“…The initial analysis of G␣ i3 -deficient mice did not reveal overt phenotypic defects (5,6). However, the comparative analysis of G␣ i1 /G␣ i3 -double-deficient with G␣ i2 -deficient mice led to the identification of overlapping as well as gene-specific functions of G i isoforms in the antiinfectious response of macrophages and splenocytes (7). Recent studies of G␣ i3 mutant mice have revealed craniofacial and other skeletal deformities consistent with a specific requirement for G␣ i3 in the cranial neural crest and in somites (N. W. Plummer, K.S., J. Malphurs, L.B., unpublished work).…”
mentioning
confidence: 99%